Analysis of the relationship between hip joint flexion/extension and torques in the mark III space suit using a computational dynamics model. Issue 8 (11th June 2021) - McKeen, Patrick; Cullinane, Conor; Rhodes, Richard; Stirling, Leia
Abstract: Advanced SSAs (e.g., the Mark III (MKIII)) were designed to increase mobility by eliminating the volume change associated with bending joints by using constant-volume rigid components with bearings connecting these components. Even with these changes, there are added torques required by the operator to drive the motion, which increases the energy expenditure with respect to unsuited motion. Part of the added effort stems from the mass and inertia of the suit, as well as frictional resistances to motion. This research considers the relationship between joint torques that an operator must generate and the resulting flexion/extension of the hip bearing assembly. A computational dynamics model of the MKIII inclusive of inertial and bearing friction properties was created and sensitivities of the model to input parameters (e.g., applied force, direction of gravity, bearing friction magnitude, knee angle) were investigated. The model was configured to match previously collected benchtop experimental suit data without a human that was externally forced. The model captured the hysteretic behaviour and estimated about 80% of the mean hip angle range as compared to the experimental data. Decreasing bearing resistance increased alignment with the experimental data. The torque due to inertia and friction each had periods where they dominated the total torque, supporting the importance of minimizing both mass and bearing friction. The present effort also highlighted how external forces and boundary conditions affected peak hip flexion/extension. Future efforts can use these types of dynamics models to examine motions driven internally by a person to achieve specific motions.